Applying the opportunity perspective to corporate offending and victimization - Benson, Michael L. (Corporate crime, 2026)
The opportunity perspective assumes that the presence of conditions conducive to crime is an essential predicate of crime. This perspective has been applied primarily to “street” crimes. In this chapter, however, we explore how it can be applied to corporate crimes. The theoretical foundations of the opportunity perspective are explicated and then the approach is applied to three specific forms of corporate wrongdoing - antitrust offenses, healthcare fraud, and environmental crimes. Research on corporations as both offenders and victims is reviewed and some preliminary suggestions on how to use the opportunity perspective to control corporate offending are presented.